Complete history of the world. edited by geoffrey barraclough - Overy, Richard J. ([S.l.] : Times Books, 2010)
The ultimate work of historical reference From cavemen to the Cold War, from Alexander the Great to global warming, from warfare through the ages to the great voyages of exploration, The Times Complete History of the World is the book that has all the answers. This is the most comprehensive, authoritative and accessible work on world history available today. It has sold over 2.25million copies and has been translated into 18 other languages since its first publication in 1978. With a narrative scope covering the origins of mankind right through to the turmoil of the 21st century, this book is an unrivalled and breathtaking accomplishment. With over 600 full-colour maps and charts on a wide range of historical subjects and representing the work of a team of professional historians, this new edition continues a tradition of nearly thirty years of excellence, style, authority and cutting-edge design. This edition is also internet-linked. Readers can follow the weblinks in the book to acess the most up to date information permitting further in-depth exploration of key subjects. With fully up-to-date text, including material on Iraq and Afghanistan, terrorism, Israel and the EU, this book, edited by leading modern historian Professor Richard Overy, is broad-ranging and more visually enticing than ever. Updates for the eighth edition include: - New material on the United States - The most up-to-date research on prehistory - Reworked spreads on the Middle East, including a new spread on Iran - Current information on the global economy, the global environment, warfare and world terrorism - New introduction - Short biographies of 100 key figures in world history.